Pelatihan Pembuatan Lembar Kerja Peserta Didik Elektronik Berbantuan E-Worksheet Interaktif - Muhammad Irfan Rumasoreng; Arie Purwanto; Hilliyani (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
Teachers of Muhmmadiyah Mlati High School experience obstacles in making interactive student worksheets and can do a quick assessment of student learning outcomes. An interactive e-worksheet is an electronic worksheet that can be used by students to learn interactively. This service aims to help teachers make e-worksheet-based LKPD so that it can interactively improve learning outcomes. The method used is community-based research. Based on the training results, there was a positive response with all teachers able to use e-worksheets during training according to the material taught.